Programmed immunoadsorption with regeneration of adsoption columns in the treatment of lupus nephritis - A. A. Sokolov; A. S. Manuilov; S. N. Bardakov; V. V. Tishko; A. N. Belskikh; O. Yu. Strelnikova; T. V. Bulgakova (Современная ревматология)
Programmed immunoadsorption (IA) with regeneration of adsoption columns is a promising and safe technique to treat lupus nephritis (LN) in case of ineffective immunosuppressive therapy and its severe adverse reactions. This technique makes it possible to control disease activity, to maintain kidney function, and to ensure a normal quality of life. Due to the reusability of IA columns, it is possible to remove any required amount of IgG and to reduce the cost of an extracorporeal procedure.The paper describes a clinical case of 3-year prolonged IA in a female patient with systemic lupus erythematosus (SLE) and LN with the insufficient efficacy of drug therapy and related complications. Seventy IA sessions were performed during a follow-up period. Combined treatment with glucocorticoids, cytotoxic drugs, and IA resulted in improved clinical and laboratory parameters, lower SLE activity according to SELENA-SLEDAI scores, and better quality of life according to the SF-36 scale. No adverse reactions were recorded during IA sessions.